Endothelial nitric oxide synthase traffic inducer (NOSTRIN) is a negative regulator of disease aggressiveness in pancreatic cancer - Wang, Jian; Gaida, Matthias (Clinical cancer research, 2016)
Purpose: Pancreatic ductal adenocarcinoma (PDAC) is refractory to available treatments. Delineating critical pathways, responsible for disease aggressiveness and therapeutic resistance, may identify effective therapeutic targets. We aimed to identify key pathways contributing to disease aggressiveness by comparing gene expression profiles of tumors from early-stage PDAC cases with extremely poor survival (≤7 months) and those surviving 2 years or more following surgical resection. Experimental Design: Gene expression profiling was performed in tumors in a test cohort of PDAC (N = 50), which included short (≤7 months, N = 11) and long surviving (≥2 years, N = 14) patients, using affymetrix GeneChip Human 1.0 ST array. Key genes associated with disease aggressiveness were identified, using Cox regression, Kaplan-Meier, and pathway analyses with validations in independent cohorts for mechanistic and functional analyses. Results: Gene expression profiling identified 1,820 differentially expressed genes between short and long survival groups with inflammatory gene network ranking first. Lower expression of endothelial nitric oxide synthase traffic inducer (NOSTRIN) was associated with worst survival indicating its potential inhibitory role in disease progression. NOSTRIN overexpression suppressed migration and invasion of pancreatic cancer cells and enhanced sensitivity to chemotherapeutic drug gemcitabine. NOSTRIN inhibited production of nitric oxide (NO) by suppressing the activation of endothelial nitric oxide synthase (eNOS). Furthermore, miR-221, bound to the 3′UTR of NOSTRIN and suppressed its expression, and an increased miR-221 expression associated with poor survival in PDAC. Conclusions: Our findings showed that NOSTRIN is a potential negative regulator of disease aggressiveness, which may be targeted for designing improved treatment strategy in PDAC. Clin Cancer Res; 22(24); 5992-6001. ©2016 AACR.